2014
DOI: 10.1515/epoly-2013-0001
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrrole microcontainer structures and doughnuts designed by electrochemical oxidation: an electrochemical and scanning electron microscopy study

Abstract: Scanning electron microscopy (SEM) is employed to monitor the surface morphology of poly pyrrole films (PPy) grown on different working electrodes (i.e., vitreous carbon and Au (111)) under diverse experimental conditions (i.e., dynamic vs. static potential protocols) and anion dopants (i.e., I -and F -). The morphology of the electrosynthesized films includes rings (doughnuts) and microcontainers, and depends on the synthesis parameters such as the electropolymerization method, the nature of the substrate, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The influence of anions and solution pH on PPy micro-and nanostructures obtained preferably without a template has been discussed [105,106], and possible overoxidation depending on the particular experimental conditions and actual interfacial situation was addressed. The formation of PPy microcontainer and doughnut structures prepared via various electrochemical procedures with different anions was attributed to the overoxidation of fluoride-containing polymer [107]. Unintended overoxidation possibly resulting in PPy with lower electronic conductivity was examined as a conceivable reason for the existence of maximum conductivity [108].…”
Section: Ppymentioning
confidence: 99%
“…The influence of anions and solution pH on PPy micro-and nanostructures obtained preferably without a template has been discussed [105,106], and possible overoxidation depending on the particular experimental conditions and actual interfacial situation was addressed. The formation of PPy microcontainer and doughnut structures prepared via various electrochemical procedures with different anions was attributed to the overoxidation of fluoride-containing polymer [107]. Unintended overoxidation possibly resulting in PPy with lower electronic conductivity was examined as a conceivable reason for the existence of maximum conductivity [108].…”
Section: Ppymentioning
confidence: 99%
“…The morphological study revealed that the conditions induced ring (doughnuts) and microcontainer formation. The microstructure formation was contingent on the occurrence of the overoxidation of PPy [200]. The polypyrrole morphology showed significant influence on the BET surface in the studies of Mosch [201], where the porosity and surface measurements revealed the increase in average pore size for composites in comparison to pure carbons (either CB or MWCNT).…”
Section: As Carbon-based Materialsmentioning
confidence: 98%
“…This seems to be true for the "marriage" of polypyrrole and carbon-based materials, where attempts to provide new materials are highly successful and promising. Different carbon-based substrates (vitreous carbon and Au ( 111)) as well as various experimental conditions (dynamic vs. static potential protocols) and halogen dopants (I − and F − ) were tested in the work of Batina [200]. The morphological study revealed that the conditions induced ring (doughnuts) and microcontainer formation.…”
Section: As Carbon-based Materialsmentioning
confidence: 99%
“…During my research, at some point we got involved in the direct and indirect reduction of chromate ions by a conductive polymer, and -for something that can be attributed to serendipity -we achieved a patent [9]. We also published several works on the subject thanks to a collaboration with Nikola Batina of the UAM-I, Arturo Fregoso of Ibero, as well as Silvia Gutiérrez, Alejandro Alatorre, Ulises Páramo, Javier Guzmán and Francisco Rodríguez of the University of Guanajuato, in addition to several students [10,11]. With the same Alejandro Alatorre and collaborators, we later developed our idea of evaluating the possibility of using Ag(III) compounds for remediation purposes as it is a powerful oxidant [12].…”
Section: Foray Into Environmental Electrochemistrymentioning
confidence: 99%